The Grassroots Development in Nigeria: The Implications of Grassroots Development Theory in Development Policy Making in Nigeria - Ghufrony, Fara Kamilah (UNIDA GONTOR, 2024)
This research explores the implications of the Grassroots Development Theory in shaping development policy in Nigeria. The study identifies key challenges including economic inequality, corruption, regional disparities, and social conflicts that hinder inclusive and sustainable development in the country. The primary aim is to analyze the practical application of Grassroots Development Theory in addressing these challenges and promoting holistic development. To achieve this, a descriptive qualitative research method is employed, involving an extensive literature review encompassing scientific journals, books, research reports, government policies, and relevant literature sources. The findings of this study shed light on the potential of Grassroots Development Theory to guide policy formulation for more inclusive and equitable development in Nigeria.The research concludes that a deep understanding of these challenges and a commitment to addressing them collectively are essential for Nigeria to achieve inclusive, sustainable, and peaceful development for its entire population. The study recommends further research focusing on concrete impacts, comparative analysis with similar nations, participatory research to understand local perspectives, and policy analysis, particularly in the areas of education and grassroots skill development.